Catalyst for harmless treatment of solid waste phosphogypsum and harmless treatment method
By using a catalyst composed of glass powder, amorphous silica and borax in the treatment of phosphogypsum, the phosphogypsum is calcined at low and medium temperature, which solves the problems of high energy consumption and complex process caused by high temperature calcination, and realizes the cycle of resources Reduced utilization and production costs.
Patent Information
- Application Number
- CN202411576119.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, when phosphogypsum is treated harmlessly, high temperature calcination (such as 2100°C), resulting in high energy consumption and high cost, complex process, and problems of cumbersome operation and waste of resources.
A catalyst for harmless treatment of solid waste phosphogypsum is designed. The catalyst consists of glass powder, amorphous silica and borax. The phosphogypsum is treated by low-medium temperature calcination (about 1370℃) to generate sulfuric acid that can be used in industry and construction. and construction sand.
The decomposition temperature of phosphogypsum is reduced, energy consumption and production costs are significantly reduced, process steps are simplified, and the recycling of resources is realized, and the resulting products can be stacked directly or used in construction and industry.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of phosphogypsum treatment, and specifically relates to a catalyst and a harmless treatment method for solid waste phosphogypsum. Background Art
[0002] Solid waste phosphogypsum, also known as industrial calcium phosphate, desulfurized phosphogypsum, etc., is a solid waste generated in the wet phosphoric acid process; phosphogypsum contains impurities such as fluoride, free phosphoric acid, P2O5, and phosphates. These substances may enter the water body through rainwater leaching during storage, causing water pollution. Fluoride, in particular, has potential hazards to aquatic organisms and human health; and long-term storage of phosphogypsum may also pollute the surrounding soil through wind erosion, rain erosion, etc., affecting soil quality; therefore, it needs to be effectively treated harmlessly to avoid environmental pollution.
[0003] At present, there are corresponding methods for treating phosphogypsum. For example, the patent with patent publication number CN117102220A discloses a phosphogypsum curing agent and a harmless treatment method for phosphogypsum. Based on the principle of "co-precipitation-netting", slag and high-silicon-aluminum solid waste are activated by alkaline activators, and the generated CaF2 is coated to reduce its contact area in water, so that the F in the treated phosphogypsum can be stably up to standard, which effectively handles the problem of solid phosphogypsum. However, it is necessary to treat the phosphogypsum into a slurry, and to add a precipitant, a netting agent, etc. The operation process is cumbersome and still has defects to a certain extent. At the same time, the patent with patent publication number CN116477654A discloses a harmless treatment method for phosphogypsum, which converts its phosphorus by adding quicklime for treatment, and disperses the phosphogypsum and then The phosphogypsum is rendered harmless by pickling with hydrochloric acid; however, this method not only requires the purchase of additional hydrochloric acid for acidification, but also requires strict control of parameters in each process, and there are still defects to a certain extent; in addition, the patent publication number CN112142350B discloses a phosphogypsum desulfurization calcination treatment system and treatment method, which uses coal and coke as reducing agents to burn phosphogypsum in a rotary kiln to generate CaS, CaO, SO2, CO2 and CO gases, and further converts CO into CO2 and removes S to achieve the purpose of evolution, but this method will produce other gases, which need to be treated, which undoubtedly increases the process treatment. In addition, when phosphogypsum is calcined in the prior art, the temperature needs to be increased to 2100°C, which has high energy consumption and no economic value.
[0004] Therefore, a catalyst and a harmless treatment method for solid waste phosphogypsum are needed to solve the above technical problems. Summary of the invention
[0005] In order to solve the above technical problems, the present invention designs a catalyst and a harmless treatment method for solid waste phosphogypsum, which does not require excessive treatment of phosphogypsum, and introduces a catalyst into it, directly treats the phosphogypsum harmlessly through low-medium temperature calcination, and the final product can be directly stacked, and sulfuric acid can be generated and directly used in industry; this method can reduce the decomposition temperature to about 1370°C. It greatly reduces energy consumption, significantly reduces production costs, and solves the problem of high cost and no benefit of industrial production of sulfuric acid from solid waste phosphogypsum; the residue after producing sulfuric acid meets the standard for building silicon sand, can be used in concrete pouring, highway construction, building materials and other industries, and can achieve harmless treatment.
[0006] In order to achieve the above technical effects, the present invention discloses a catalyst for harmless treatment of solid waste phosphogypsum, which is composed of 12-18% glass powder, 0.5-1% amorphous silicon dioxide, and 0.5-1% borax in percentage; Further, the catalyst is composed of 15% glass powder, 0.5% amorphous silicon dioxide, and 0.5% borax in percentage; On the other hand, the present invention provides a method for harmless treatment of solid waste phosphogypsum, comprising the following steps: S1: Raw material preparation: Dehydrate the phosphogypsum into hemihydrate gypsum through a rotary dryer or a rapid airflow drying device; S2: Raw material preparation: Add catalyst to the dehydrated phosphogypsum (hemihydrate gypsum) to prepare raw material; S3: Pretreatment: After homogenization and metering, the raw material is sent to a four-stage cyclone preheater for preheating for 1 hour at a temperature of 300°C; S4: High temperature calcination: The preheated raw material enters the rotary kiln for high temperature calcination. The calcination temperature is 1370℃ and the calcination time is 3 hours. S5: Flue gas treatment and sulfuric acid production: The sulfur-containing flue gas at the kiln tail is purified and dried by the electrostatic precipitator and enters the two-transfer and two-absorption system; under the action of the catalyst, the SO2 in it is converted into SO3, and the SO3 is absorbed to obtain sulfuric acid; S6: Tail gas treatment: Tail gas is neutralized with ammonia before being discharged in compliance with emission standards.
[0007] Furthermore, the glass powder in the catalyst has a particle size of greater than or equal to 200 meshes, a content of amorphous silicon dioxide is greater than or equal to 95%, and a content of borax is greater than or equal to 98%; Furthermore, during the preheating in S3, the preheating temperature is 300° C. and the preheating time is 1 hour.
[0008] The beneficial effects of the present invention are: The invention discloses a catalyst for harmless treatment of solid waste phosphogypsum and a harmless treatment method. Specifically, the phosphogypsum is harmlessly treated by introducing a catalyst and directly calcining at low or medium temperatures, specifically by introducing 15% of glass powder, 0.5% of amorphous silicon dioxide and 0.5% of borax; when the phosphogypsum is directly calcined, the calcination temperature is greatly reduced, and one of the two final products can be directly stacked or used in the construction industry, and the other can be used in industry, thereby realizing the recycling of resources. Compared with the traditional direct calcination method, the calcination temperature is reduced from 2100° C. to 1370° C., thereby greatly reducing energy consumption and significantly reducing production costs. In addition, the preparation method for treating solid waste phosphogypsum in the present invention is simple, does not need to use additional chemical substances to treat it, can directly generate materials that can be used in industry and construction, and the operation process is simple. DETAILED DESCRIPTION Example 1
[0009] The invention discloses a method for harmlessly treating solid waste phosphogypsum, comprising the following steps: S1: Raw material preparation: 1000 kg of phosphogypsum is dehydrated into hemihydrate gypsum through a rotary dryer or a rapid airflow drying device; S2: Raw material preparation: Add a catalyst to the dehydrated phosphogypsum (semi-hydrated gypsum) to prepare the raw material; the catalyst percentage is composed of 15% glass powder, 0.5% amorphous silicon dioxide, and 0.5% borax; the glass powder particle fineness is greater than or equal to 200 mesh, the content of amorphous silicon dioxide is greater than or equal to 95%, and the content of borax is greater than or equal to 98% S3: Pretreatment: After homogenization and metering, the raw material is sent to a four-stage cyclone preheater for preheating for 1 hour at a temperature of 300°C; S4: High temperature calcination: The preheated raw material enters the rotary kiln for high temperature calcination. The calcination temperature is 1370℃ and the calcination time is 3 hours. S5: Flue gas treatment and sulfuric acid production: The sulfur-containing flue gas at the kiln tail is purified and dried by an electrostatic precipitator and enters a two-turn and two-absorption system; under the action of a catalyst, the SO2 therein is converted into SO3, and sulfuric acid is obtained after SO3 is absorbed; the treatment method thereof is the treatment method of the prior art and will not be further explained here.
[0010] S6: Tail gas treatment: Tail gas is neutralized with ammonia before being discharged in compliance with emission standards.
[0011] In order to further verify the content of each component of the final product of this method, the main components of the residue after the phosphogypsum is rendered harmless are detected by this method using gypsum chemical analysis method and cement chemical analysis method. Specifically, the test results are shown in Table 1 below. Table 1 Composition test results after calcination with 15% glass powder, 0.5% amorphous silicon dioxide and 0.5% borax As can be seen from the table above, the content of calcium sulfate dihydrate crystals is 0.14%, which is almost non-existent, and it is converted into "calcium silicon polymer"; the sulfur trioxide content is 0.65%, indicating that the sulfur ions in calcium sulfate are basically converted into gas and overflow. At 1370℃, solid waste phosphogypsum is decomposed into calcium silicon polymer building application materials, and sulfur trioxide can be produced as sulfuric acid for industrial applications. Example 2
[0012] In this embodiment, a catalyst and a harmless treatment method for solid waste phosphogypsum include the following steps: S1: Raw material preparation: 1000 kg of phosphogypsum is dehydrated into hemihydrate gypsum through a rotary dryer or a rapid airflow drying device; S2: Raw material preparation: Add a catalyst to the dehydrated phosphogypsum (semi-hydrated gypsum) to prepare the raw material; the catalyst is composed of 0.5% amorphous silicon dioxide and 0.5% borax in percentage; the content of amorphous silicon dioxide is greater than or equal to 95%, and the content of borax is greater than or equal to 98% S3: Pretreatment: After the raw material is homogenized and metered, it is sent to the four-stage cyclone preheater for preheating; S3: Pretreatment: After homogenization and metering, the raw material is sent to a four-stage cyclone preheater for preheating for 1 hour at a temperature of 300°C; S4: High temperature calcination: The preheated raw material enters the rotary kiln for high temperature calcination. The calcination temperature is 2100℃ and the calcination time is 3 hours. S5: Flue gas treatment and sulfuric acid production: The sulfur-containing flue gas at the kiln tail is purified and dried by an electrostatic precipitator and enters a two-turn and two-absorption system; under the action of a catalyst, the SO2 therein is converted into SO3, and sulfuric acid is obtained after SO3 is absorbed; the treatment method thereof is the treatment method of the prior art and will not be further explained here.
[0013] S6: Tail gas treatment: Tail gas is neutralized with ammonia before being discharged in compliance with emission standards.
[0014] In order to further verify the content of the components of the final product of this method, the main components of the residue after the phosphogypsum is rendered harmless are detected by this method using the gypsum chemical analysis method and the cement chemical analysis method. Specifically, the test results are shown in Table 2 below: Table 2 Results of residue composition testing when using borax and amorphous silica catalysts It can be seen from the above table that calcium sulfate dihydrate crystals are almost non-existent, and are then converted into "calcium oxide", the impurity content is reduced, and the final sulfur trioxide and calcium sulfate dihydrate are higher than the content in Example 1; and to achieve this effect, the calcination decomposition temperature must reach 2100°C, which has high energy consumption, no economic value, and does not conform to the industrial policy of energy conservation and emission reduction. Example 3
[0015] In this embodiment, a catalyst and a harmless treatment method for solid waste phosphogypsum include the following steps: S1: Raw material preparation: 1000 kg of phosphogypsum is dehydrated into hemihydrate gypsum through a rotary dryer or a rapid airflow drying device; S2: Raw material preparation: Add a catalyst to the dehydrated phosphogypsum (semi-hydrated gypsum) to prepare the raw material; the catalyst percentage is composed of 15% glass powder and 0.5% amorphous silicon dioxide; the glass powder particle fineness is greater than or equal to 200 mesh, and the content of amorphous silicon dioxide is greater than or equal to 95% S3: Pretreatment: After homogenization and metering, the raw material is sent to a four-stage cyclone preheater for preheating for 1 hour at a temperature of 300°C; S4: High temperature calcination: The preheated raw material enters the rotary kiln for high temperature calcination at a temperature of 1500°C for 3 hours; S5: Flue gas treatment and sulfuric acid production: The sulfur-containing flue gas at the kiln tail is purified and dried by an electrostatic precipitator and enters a two-turn and two-absorption system; under the action of a catalyst, the SO2 therein is converted into SO3, and the SO3 is absorbed to obtain sulfuric acid; the treatment method thereof is the treatment method of the prior art, and no further explanation will be given for each group.
[0016] S6: Tail gas treatment: Tail gas is neutralized with ammonia before being discharged in compliance with emission standards.
[0017] In order to further verify the content of each component of the final product of this method, the main components of the residue after the phosphogypsum is rendered harmless are detected by this method using gypsum chemical analysis method and cement chemical analysis method. Specifically, the test results are shown in Table 3 below. Table 3 Results of residue composition testing when using glass powder and amorphous silica catalyst As can be seen from the table above, calcium sulfate dihydrate crystals are almost non-existent, and are converted into "calcium silicon polymers"; however, the sulfur trioxide content increases to 1.25%, which shows that when 15% glass powder and 0.5% amorphous silicon dioxide are used, the sulfur trioxide content of the final product increases; at the same time, the calcination temperature is 1500°C, which consumes a lot of energy and has no economic value. Example 4
[0018] In this embodiment, a catalyst and a harmless treatment method for solid waste phosphogypsum include the following steps: S1: Raw material preparation: 1000 kg of phosphogypsum is dehydrated into hemihydrate gypsum through a rotary dryer or a rapid airflow drying device; S2: Raw material preparation: Add a catalyst to the dehydrated phosphogypsum (semi-hydrated gypsum) to prepare the raw material; the catalyst percentage is composed of 15% glass powder and 0.5% borax; the glass powder particle size is greater than or equal to 200 mesh, and the borax content is greater than or equal to 98% S3: Pretreatment: After homogenization and metering, the raw material is sent to a four-stage cyclone preheater for preheating for 1 hour at a temperature of 300°C; S4: High temperature calcination: The preheated raw material enters the rotary kiln for high temperature calcination at a temperature of 1500°C for 3 hours; S5: Flue gas treatment and sulfuric acid production: The sulfur-containing flue gas at the kiln tail is purified and dried by an electrostatic precipitator and enters a two-turn and two-absorption system; under the action of a catalyst, the SO2 therein is converted into SO3, and sulfuric acid is obtained after SO3 is absorbed; the treatment method thereof is the treatment method of the prior art and will not be further explained here.
[0019] S6: Tail gas treatment: Tail gas is neutralized with ammonia and then discharged in compliance with the emission standards. Each group further verified the content of each component of the final product of this method. Now, using the gypsum chemical analysis method and cement chemical analysis method, the main components of the residue after the phosphogypsum is rendered harmless are detected by this method. Specifically, the test results are shown in Table 4 below. Table 4 Detection results of residue components when using glass powder and borax catalyst It can be seen from the above table that the content of calcium sulfate dihydrate crystals is 0.36%, and the rest is converted into "calcium silicon polymer"; however, the sulfur trioxide content increases to 3.12%, and the required calcination temperature is 1500°C; this shows that when using 15% glass powder and 0.5% borax, the content of sulfur trioxide in the final product will increase, and it will be more troublesome in the final sulfuric acid production and processing, requiring a lot of long-term process treatment to consume it. Example 5
[0020] In this embodiment, the catalyst percentage is composed of 15% glass powder, and the rest of the process is the same as in Example 1; the calcination temperature is 1500°C through experiments. The final content of calcium sulfate dihydrate crystals is 0.41%, and the content of sulfur trioxide is 3.7%. The results are obtained using gypsum chemical analysis method and cement chemical analysis method. Example 6
[0021] In this embodiment, the catalyst is composed of 0.5% amorphous silicon dioxide, and the rest of the process is the same as in Example 1; the calcination temperature is 1500°C as determined by experiments. The final content of calcium sulfate dihydrate crystals is 11.2%, and the content of sulfur trioxide is 23%. This is determined by gypsum chemical analysis and cement chemical analysis. Example 7
[0022] In this embodiment, the catalyst percentage is composed of 0.5% borax, and the rest of the process is the same as in Example 1; the calcination temperature is 1500°C through experiments. The final content of calcium sulfate dihydrate crystals is 13.7%, and the content of sulfur trioxide is 26.1%. The results are obtained using gypsum chemical analysis method and cement chemical analysis method.
[0023] In summary, when using catalysts, borax, amorphous silica, and glass powder alone, the final calcium sulfate dihydrate crystals and sulfur trioxide products have a relatively high ratio, and the calcination temperature is above 1500°C, which has high requirements for calcination and extremely high energy consumption.
[0024] Comparative Example 1 In this example, the optimal calcination temperature and the catalyst used are obtained based on the specific comparison of Examples 1 to 7 as described in Example 1, and the content used is further verified; the verification process is as follows; S1: Raw material preparation: 1000 kg of phosphogypsum is dehydrated into hemihydrate gypsum through a rotary dryer or a rapid airflow drying device; S2: Raw material preparation: Add a catalyst to the dehydrated phosphogypsum (semi-hydrated gypsum) to prepare the raw material; the catalyst percentage is composed of 12% glass powder, 0.5% amorphous silicon dioxide, and 0.5% borax; the glass powder particle fineness is greater than or equal to 200 mesh, the content of amorphous silicon dioxide is greater than or equal to 95%, and the content of borax is greater than or equal to 98% S3: Pretreatment: After homogenization and metering, the raw material is sent to a four-stage cyclone preheater for preheating for 1 hour at a temperature of 300°C; S4: High temperature calcination: The preheated raw material enters the rotary kiln for high temperature calcination. The calcination temperature is 1370℃ and the calcination time is 3 hours. S5: Flue gas treatment and sulfuric acid production: The sulfur-containing flue gas at the kiln tail is purified and dried by an electrostatic precipitator and enters a two-turn and two-absorption system; under the action of a catalyst, the SO2 therein is converted into SO3, and sulfuric acid is obtained after SO3 is absorbed; the treatment method thereof is the treatment method of the prior art and will not be further explained here.
[0025] S6: Tail gas treatment: Tail gas is neutralized with ammonia before being discharged in compliance with emission standards.
[0026] Comparative Example 2 S1: Raw material preparation: 1000 kg of phosphogypsum is dehydrated into hemihydrate gypsum through a rotary dryer or a rapid airflow drying device; S2: Raw material preparation: Add a catalyst to the dehydrated phosphogypsum (semi-hydrated gypsum) to prepare the raw material; the catalyst is composed of 18% glass powder, 1% amorphous silicon dioxide, and 1% borax in percentage; the glass powder particle size is greater than or equal to 200 mesh, the content of amorphous silicon dioxide is greater than or equal to 95%, and the content of borax is greater than or equal to 98% S3: Pretreatment: After homogenization and metering, the raw material is sent to a four-stage cyclone preheater for preheating for 1 hour at a temperature of 300°C; S4: High temperature calcination: The preheated raw material enters the rotary kiln for high temperature calcination. The calcination temperature is 1370℃ and the calcination time is 3 hours. S5: Flue gas treatment and sulfuric acid production: The sulfur-containing flue gas at the kiln tail is purified and dried by an electrostatic precipitator and enters a two-turn and two-absorption system; under the action of a catalyst, the SO2 therein is converted into SO3, and sulfuric acid is obtained after SO3 is absorbed; the treatment method thereof is the treatment method of the prior art and will not be further explained here.
[0027] S6: Tail gas treatment: Tail gas is neutralized with ammonia before being discharged in compliance with emission standards.
[0028] Similarly, the main components of the residue after the phosphogypsum was rendered harmless were detected by this method using the gypsum chemical analysis method and the cement chemical analysis method. Specifically, the test results are shown in Table 5 below. Table 5 Residue composition test results when using glass powder, amorphous silica and borax catalyst It can be seen from the table above that the content of calcium sulfate dihydrate crystals is 0.18%, and the rest is converted into "calcium silicon polymer"; sulfur trioxide is 0.69%, and the required calcination temperature is 1370°C; this shows that when using 18% glass powder, 1% amorphous silicon dioxide, and 1% borax, the final product is not much different from Example 1; the results are similar; At the same time, the content of the catalyst used was changed again. The catalyst percentage was composed of 20% glass powder, 1.5% amorphous silicon dioxide, and 1.5% borax; the glass powder particle size was greater than or equal to 200 mesh, the content of amorphous silicon dioxide was greater than or equal to 95%, and the content of borax was greater than or equal to 98%. The main components of the residue after the phosphogypsum was rendered harmless were detected by the present method using the gypsum chemical analysis method and cement chemical analysis method. Specifically, the test results are shown in Table 6 below: Table 6 Results of residue composition when using a large percentage of glass powder, amorphous silica and borax catalyst As can be seen from the table above, the content of calcium sulfate dihydrate crystals has increased to 0.53% compared with the content in Table 5, and sulfur trioxide has also increased to 7.59%. This shows that when using 20% glass powder, 1.5% amorphous silicon dioxide, and 1.5% borax, the content of the final product increases; the reason is that the final product of the decomposition of solid waste phosphogypsum is similar to "volcanic magma inclusions"; from the side, it can be reflected that the best usage ratio is 12-18% glass powder, 0.5-1% amorphous silicon dioxide, and 0.5-1% borax.
[0029] Based on the above embodiments and comparative examples, the phosphogypsum is harmlessly treated by introducing a catalyst and directly calcining at low to medium temperatures, specifically by introducing 15% glass powder, 0.5% amorphous silicon dioxide, and 0.5% borax; when it is directly calcined, the calcination temperature is greatly reduced, because the combination of the three catalysts in a specific proportion used greatly reduces the temperature under their synergistic effect, thus solving the problem of high energy consumption caused by the need for ultra-high temperature when calcining phosphogypsum in the traditional way; And one of the two final products can be directly stacked or used in the construction industry, and the other can be used in industry, realizing the recycling of resources. The temperature is significantly reduced from the traditional 2100°C to 1370°C, which is a significant improvement. The simple process steps can be used for the process treatment of solid waste phosphogypsum, and the treatment of phosphogypsum has great prospects.
[0030] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only the specific implementation methods described.
Claims
1. A catalyst for harmless treatment of solid waste phosphogypsum, characterized in that: In terms of percentage, it is composed of 12-18% glass powder, 0.5-1% amorphous silicon dioxide and 0.5-1% borax.
2. The catalyst for harmless treatment of solid waste phosphogypsum according to claim 1, characterized in that: The catalyst consists of 15% glass powder, 0.5% amorphous silicon dioxide and 0.5% borax in percentage.
3. A method for harmlessly treating solid waste phosphogypsum using the catalyst according to claim 1 or 2, characterized in that: The following steps are involved: S1: Raw material preparation: Dehydrate the phosphogypsum into hemihydrate gypsum through a rotary dryer or a rapid airflow drying device; S2: Raw material preparation: Add catalyst to the dehydrated phosphogypsum to prepare raw material; S3: Pretreatment: After homogenization and metering, the raw material is sent to a four-stage cyclone preheater for preheating for 1 hour at a temperature of 300°C; S4: High temperature calcination: The preheated raw material enters the rotary kiln for high temperature calcination. The calcination temperature is 1370℃ and the calcination time is 3 hours. S5: Flue gas treatment and sulfuric acid production: The sulfur-containing flue gas at the kiln tail is purified and dried by the electrostatic precipitator and enters the two-transfer and two-absorption system; under the action of the catalyst, the SO2 in it is converted into SO3, and the SO3 is absorbed to obtain sulfuric acid; S6: Tail gas treatment: Tail gas is neutralized with ammonia before being discharged in compliance with emission standards.
4. The method for harmlessly treating solid waste phosphogypsum according to claim 3, characterized in that: The glass powder particle fineness in the catalyst is greater than or equal to 200 meshes, the content of amorphous silicon dioxide is greater than or equal to 95%, and the content of borax is greater than or equal to 98%.
5. The method for harmlessly treating solid waste phosphogypsum according to claim 3, characterized in that: During the preheating in S3, the preheating temperature is 300° C. and the preheating time is 1 hour.
Citation Information
Patent Citations
Phosphogypsum desulfurization calcination treatment system and treatment method
CN112142350B
Harmless treatment method of phosphogypsum
CN116477654A
Phosphogypsum curing agent and phosphogypsum harmless treatment method
CN117102220A